(untitled) (Revista Espacio Regional, 2024)
The article present ethnographic findings on the transnational migration of inhabitants of Chiloe Island, Chile, to Ushuaia, Tierra del Fuego, Argentina, in three generational ages from 1947 to 2018. The first age focuses on the closure of the Ushuaia prison as a driver of foreign migration, particularly in the case of early settlements of Chilotes seeking seasonal employment. The second age reflects a large-scale displacement of rural families associated with various ecological, political, and economic events which took place in Chiloe. A third age relates to permanent settlements of Chilotes on the outskirts of the town, the construction of the notion of «home», and the circulation of cultural practices that served to lend legitimacy to the community. The key findings show how these displacements in Ushuaia occurred later in comparison to other Fuego-Patagonian towns —such as Río Grande and Río Gallegos, which had been receiving migrants from Chiloe since 1890—, especially those that inspired male migration associated with seasonal employment in places like ranches (estancias), meat-packing plants, and fat-rendering plants.